PROSES PELAKSANAAN EVENT MEETING DI BANQUET SECTION HOTEL PREMIERE PEKANBARU - Andriani "; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine (1) how the process of meeting event implementation in premiere hotel Pekanbaru, (2) how to overcome obstacles in the implementation of the event meeting in banquet section hotel premiere pekanbaru. The design of this study is qualitative descriptive. The subjects of this study are key informants and additional informants. Key informants are, sales banquet marketing hotel premiere pekanbaru and additional informant that is one employee per department hotel premiere pekanbaru. Data collection techniques used were observation, documentation, in-depth interviews and document studiesFrom the results of research that has been related to the author of the implementation of the event meeting in banquet section premiere hotel Pekanbaru, then taken the conclusion of the implementation of his event is good although there are still obstacles encountered. obstacles faced such as changes in the agreement of the event, the old payment, the lack of his communication, the lack of hygiene from the event organizer and his lack of order.Keywords: Event, meeting, banquet